Pengaruh STAD Berbantu Kartu Kuartet Terhadap Hasil Belajar IPA Kelas IV SDN 5 Kota Bengkulu - Marshella, Tiara Sonya (Universitas Bengkulu, 2024)
This study examined the effects of using the STAD cooperative learning model using quartet card media on students' learning outcomes in Class IV Elementary School 5 Bengkulu City's thematic science learning. The sole matching pretest and posttest study design was utilized in this quantitative research, which was conducted using a quasi-experimental methodology. All class IV students made up the study population, and cluster random sampling was used to choose the research samples. Written test sheets were employed as the instrument, and pretest and posttests, as well as observation sheets on the application of learning using the STAD type cooperative model supplemented by quartet card media, were utilized to gather data. Quantitative analysis was used to analyze the data that was acquired. A substantial difference between the experimental class and the control class was shown by the posttest value analysis findings. Then a tcount (2.225) > ttable (1.998) t-test was performed to evaluate the validity of the hypothesis. It can be concluded that there is an impact of the application of the cooperative learning model type STAD assisted by quartet card media on learning outcomes in the thematic learning of science content in class IV SDN 5 Bengkulu City because the tcount > ttable test results show that H0 is rejected and Ha is accepted.